Nigeria’s economic growth and The Sisyphus Odyssey: a theoretical retrospect - Lasbrey Iheanyi Anochiwa; Tobechi Agbanike; Denis Nfor Yuni; Basil Chukwu (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
We posit in the paper that getting out of Dutch disease or resource curse in Nigeria will be a mirage if the more potent disease of institutional decay, ethnicity and religious bigotry are not settled. Those who have opportunity to advice the country has over the years wrongly fixated on the rise or fall of GDP and foreign investment flows as attention is now centered on extraction industry. We recognize institutional factors as major determinants of growth in Nigeria. From our analysis it is observed that Nigeria has indeed fallen into the trap of Dutch disease and resource curse phenomenon. We also observe that Nigeria is ethnic bias and highly religious in virtually everything. And every policy of the government (economic, social or political) is weighed on the scale of religion or ethnic benefit. It is equally sad to note the quantum of resources engaged to curtail ethnic clashes as well deaths and IDPs. As Nigeria is governed by ethnic sentiments and religious bigotry , it increases the tendency for corruption and its attendant negative economic consequences. These constitute serious impediments and make the task of growth Sisyphean.